O-25 Three-year functional outcomes of ankle joint injuries' treatment in professional soccer players. (18th November 2016) - Czamara, Andrzej; Szuba, Lukasz; Królikowska, Aleksandra; Kentel, Maciej; Krupa, Sebastian; Reichert, Pawel; Sznajder, Wojciech
Abstract : Objectives: The three-year evaluation of ankle joint injuries treatment in soccer players based on the clinical examination, biomechanical tests, physical activity level, game-related statistics and Foot and Ankle Ability Measure scale (FAAM). Methods: The initial sample comprised of 162 soccer players, playing in the 1 st and 2 nd Division and European league. Twenty four of them were treated three years before because of the unilateral injuries of the ankle joint. Group I – 12 players after arthroscopically treated symptomatic anterior body impingement (ABI) as a complication of recurrent ankle sprains what was confirmed in the orthopaedic examination. Group II −12 players after conservative treatment of ankle sprains (grade I/II). The time of postoperative physiotherapy in the Group I was 14–16 weeks. The physiotherapy in the Group II lasted for 3-5 weeks after the injury. After that they returned to individual training. The first game in the Group I was played after 2–6 weeks of individual training and in the Group II after 1–2 weeks of individual training. The Group III was a control group of players without any ankle joint injuries. In the three studied groups there was performed evaluation based on the orthopaedic examination, pain assessment with the use of visual analogue scale (VAS), ankle joints range of motion measurements, ankle joints circumferences measurements, ankle dorsi- and plantar-flexion muscles relative torques (RT) measurements under isokinetic conditions. There were also performed vertical ground reaction force (vGRF) measurements during one-legged and two-legged jumps. The run-test with maximal speed and change of direction manoeuvres was performed. The return to competitive sport was assessed with the use of FAAM and basing on the game-related statistic of players. The intra-group and inter-group statistical analysis was performed. Results: There were found no statistically significant differences between the involved and uninvolved leg and the control group in the joint circumferences and in the RT of ankle dorsi- and plantar-flexion muscles. The comparison between the three groups also didn't reveal any statistically significant differences between the results of the run test, vGRF during two-legged jump values, FAAM results and in the level of professional sport participation. No pain was noted during or after the performed test. In the day of measurement, all of the players were playing on the same competitive level pre-operatively and pre-injury. There were found statistically significant differences in vGRF during one-legged jumps between involved leg in Group I and dominant leg in Group III. There was also noted limited range of foot dorsiflexion in the involved leg comparing to uninvolved one in the Group I. Conclusions: The evaluation performed three years after treatment of ankle joint injuries revealed good results in the clinical assessment, most of biomechanical tests, physical activity level and return to competitive sport assessment in players treated conservatively as well as in players after surgical intervention. Nevertheless, in players after ankle joint arthroscopy because of the ABI the range of foot dorsiflexion in the involved leg was limited which may have a meaning in ankle joint arthritis development in the future.